Testing the affective events theory: The mediating role of affect and the moderating role of mindfulness - Junça‐Silva, Ana; Pombeira, Catarina; Caetano, António (Applied cognitive psychology, 2021)
Summary This study aims to expand the knowledge on the affective events theory by: (1) testing the mediating role of affect in the relationship between micro‐daily events and well‐being, (2) and analyzing the moderating role of mindfulness in this mediated relationship. To achieve these goals, we collected data with 393 working adults. The results showed that: (1) affect mediates the relationship between micro‐daily events and well‐being; (2) mindfulness moderates the mediated relationship between micro‐daily events and well‐being via affect, that is, higher levels of mindfulness are positively related to well‐being in particular when the levels of positive affect are higher. These results show the importance of providing conditions for the occurrence of daily uplifts at work as these seem to lead to increases in employees' well‐being. Promoting mindfulness at work also seems relevant for workers' mental health and well‐being, for example, through complementary training or daily practices.